A Mixed Usability Evaluation on a Multi Criteria Group Decision Support System in Agriculture - Grigera, Julián (2018)
Decision Support Systems (DSS) help users make decisions by organizing the decision-making process in stages, dealing with several input sources. In the agricultural context, these tools are becoming more important given the variety of data that producers face, market regulations and interaction of several actors with different backgrounds. Different DSS have existed for years, but their adoption is reportedly very low, being poor usability one of the most relevant factors. While there are surveys indicating this, we have not found usability evaluations on DSS with concrete results. In this work, we evaluated decision-making in the agricultural domain using a group DSS called GRUS. We present 3 different usability evaluations: a heuristic evaluation, a user test, and an automated diagnosis.